Pertanggungjawaban Holding Company Terhadap Anak Perusahaan - Nanda Ayu Cahyanti; Rahma Dwi Pangastuti; Sumriyah Sumriyah (Jurnal Hukum dan Sosial Politik, 2023)
Group companies grow and develop and many group companies cannot be controlled so that they can result in monopolies. The monopoly will occur in networks or business relationships owned by group companies. This relationship can be understood as a legal entity that has a relationship within the grub company. This research method uses normative research, where normative legal research is research by collecting secondary data that is in accordance with the problem to be studied and then processed. The results of this study explain that the responbility of the holding company to its subsidiaries in group companies is a legal relationship related to the parent and subsidiary companyes. This legal relationship after the merger, the parent company has the authority as the majority shareholder of the subsidiary. Therefore the parent company will control the operation of the subsidiary. The parent and subsidiary companies have different articles of a of association are a positive law where if the articles of association are violated it will result in the cancellation of the transaction. If the subsidiary is sued and the subsidiary violates the law, the party who is aggrieved will be sued, namely the subsidiary because based on the law, the subsidiary has its own responbilities in running the company.